Systems approach to the study of brain damage in the very preterm newborn - Leviton, Alan; Gressens, Pierre; Wolkenhauer, Olaf; Dammann, Olaf (Frontiers in Systems Neuroscience, 2015)
Background: A systems approach to the study of brain damage in very preterm newborns has been lacking Methods: In this perspective piece, we offer encephalopathy of prematurity as an example of the complexity and interrelatedness of brain-damaging molecular processes that can be initiated inflammatory phenomena. Results: Using three transcription factors, nuclear factor-kappa B (NF-κB), Notch-1, and nuclear factor erythroid 2 related factor 2 (NRF2), we show the inter-connectedness of signaling pathways activated by some antecedents of encephalopathy of prematurity. Conclusions: We hope that as biomarkers of exposures and processes leading to brain damage in the most immature newborns become more readily available, those who apply a systems approach to the study of neuroscience can be persuaded to study the pathogenesis of brain disorders in the very preterm newborn.